THE DESIGN OF AN AUTOMATIC SAVING SYSTEM FOR ELECTRIC ENERGY IN MICROCONTROLLER-BASED PJU LIGHTS - Zainal Abidin; Affan Bachri; M. Afif Fachrudin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
At this time, almost all Public Street Lights (PJU) still use the type of mercury and SON-T lamps, even though the mercury and SON-T lamps absorb a considerable amount of electricity. Public street lighting is usually on almost all nights, and this is a waste of electricity. Public street lighting is usually on most nights and thus is a waste of electricity. Usually, when it is past midnight, the streets are quiet, so the street lighting should be reduced in intensity to save electricity.  Based on this problem, this research uses an experimental method (Experiment) to create a design to make efforts in saving electricity. The method used includes electrical and systematic design. The steps taken include the stage of literature research, designing, manufacturing hardware and software, integrating the system, and testing and analyzing the system. Considering these theories, we can know the programming of the microcontroller ATMega 328, Photocell Sensor, PIR Sensor, LED Lights, and Power Supply. This research using several tests, including testing Photocell Sensor, PIR Sensors, LDR Sensors, and LED Lights. Photocell sensor to detect conditions day or night. PIR sensor functions to detect movement, LDR sensor to detect movement, LED lights are used to increase and decrease light intensity. For all the tests above, the results obtained when the PIR and LDR sensors have not detected any movement will dim the intensity of the LED lights. After the PIR and LDR sensors have detected the movement of the LED lights, they will turn automatically bright.